Pengembangan Multimedia Pembelajaran Ramah pada Mata Pelajaran IPAS Kelas V SD - Putri, Dinda Aulia; Yusri, Meldi Ade Kurnia; Novrianti, Novrianti; Pratiwi, Rahmi (Indo-MathEdu Intellectuals Journal, 2025)
Science and Social Studies (IPAS) learning in primary schools still tends to be teacher-centred, resulting in students being less actively involved and experiencing difficulties in understanding complex concepts. Based on observations, the low level of student enthusiasm is influenced by the limited use of media, which is still restricted to textbooks and conventional media. This study aims to develop more engaging multimedia learning materials to help students understand the material in an easier and more enjoyable way. The research used the Research and Development (R&D) method with the 4-D model (Define, Design, Develop, Disseminate) through the stages of needs analysis, design, development, expert validation, limited testing, and product dissemination. The media was developed using Microsoft PowerPoint and can be accessed via Android and Windows devices. Data were obtained through validity and practicality questionnaires, which were analysed quantitatively and qualitatively. The results showed that the media was classified as ‘highly valid’ with a validity level of 98% in terms of material and 97% and 94% in terms of media, and was classified as ‘highly practical’ with a practicality score of 97% for teachers and 97.5% for students. Thus, this learning multimedia is suitable for use in improving students' focus and understanding of animal food chain material.